Acute bacterial meningitis without cerebrospinal fluid pleocytosis in children: results from a nationwide prospective surveillance system between 2001 and 2022 - Lama Jaber; Corinne Levy; Naïm Ouldali; Emmanuelle Varon; Muhamed-Kheir Taha; Stéphane Bonacorsi; Stéphane Béchet; François Angoulvant; Robert Cohen; Alexis Rybak (International Journal of Infectious Diseases)
Objectives: We aimed to describe cases of acute bacterial meningitis (ABM) without cerebrospinal fluid (CSF) pleocytosis and the clinical and biological characteristics of affected children. Methods: We analyzed results of a nation-wide population-based prospective surveillance study of acute ABM in children aged 3 months to 15 years in France. Absence of CSF pleocytosis was defined as CSF leukocyte count ≤5/mm3. Results: We included 4754 cases of acute ABM from 2001 to 2022: 173 patients (3.6%) did not have CSF pleocytosis. ABM cases without CSF pleocytosis were mainly related to meningococcus (70% vs 44% with CSF pleocytosis, P <0.001). When performed in CSF with normal leukocyte count, Gram staining results were positive for 33%, culture for 80%, polymerase chain reaction results for 41%, and antigen detection for 20% of cases. Case fatality rate was higher for cases without than those with CSF pleocytosis (18% vs 6%, P <0.001). On multivariate analysis, absence of CSF pleocytosis was associated only with seizures before hospital arrival (adjusted odds ratio 2.3, 95% confidence interval 1.2-4.6, P <0.01). Conclusions: ABM without CSF pleocytosis is infrequent but not exceptional, particularly in children with seizures before hospital arrival. Extended vaccination against meningococcus could prevent this clinical form with a high case fatality rate.